Clinical Profile And Commodities In Obese Patient (Indian Journal of Applied-Basic Medical Sciences, 2021)
Introduction: Although the terms overweight and obesity are often used interchangeably, overweight refers to an excess of body weight compared with height; obesity refers to an excess of body fat in the form of adipose tissue(adiposity). The study discusses CLINICAL PROFILE AND COMMODITIES IN OBESE PATIENT in our setup in Ahmedabad in one urban hospital. AIMS:1. To study clinical and laboratory profile of patients with obesity. 2. To asses’ comorbidities in obese patient 3. To find the age group and gender in which it is common.Material and Methods: A cross sectional study was conducted in L G Hospital Maninagar Ahmedabad in January to march 2019. Study included both outdoor and indoor patients with BMI >=30. In our study, total 200 patients were analysed for comorbidities. BMI was calculated using the expression = Weight (kilograms)/Height2 (meters). The cut off point for calculation of overweight/preobesity taken was ≥25 kg/m2 and for obesity was ≥30 kg/m2 as per the WHO 2000 guidelines. The blood pressure was recorded as per standard protocol and mean of three readings was recorded. Results: SBP, DBP, TSH and RBS were significantly elevated in obese persons. It may be concluded that a fairly high prevalence of obesity in Ahmedabad area & associated comorbidities is also more prevalent related to this. Increase in body weight may also be due to change in life style factors like fat rich food, more usage of alcohol & smoking, increased energy intake and low energy output due to less involvement of in physical activity. Discussion and CONCLUSION: The result shows higher trends of hypertension, DM2, hypothyroidism and dylipidemia with increase in BMI. Measure regarding reducing BMI reduce new incidence of such non communicable disease.
Keywords: Obese; clinical profile; Commodities in obese patient